The Essential Things of Export Network Alliances to Increase MSME Export Business Performance: The Case of Kalimantan Weaving Craft - Indriastuti, Herning; Hudayah, Syarifah; Achmad, Gusti Noorlitaria (Jurnal Dinamika Manajemen, 2025)
This study examines the role of export network alliances in bridging the gap between relational social capital and the export performance of micro, small, and medium enterprises (MSMEs). A key challenge for MSMEs in international markets is the lack of networks and relational capital, which hinders their export capabilities. Additionally, this research investigates how knowledge-sharing capabilities enhance network alliances and export performance. The study employs a purposive sampling technique, collecting data from 190 weaving craft MSMEs in Kalimantan, Indonesia, all of which have export experience. Structural Equation Modeling (SEM) with AMOS is used for analysis. The findings indicate that export network alliances significantly mediate the relationship between relational social capital, knowledge-sharing capability, and export performance. However, relational social capital alone does not directly influence export performance without the support of strong network alliances. Theoretical contributions integrate relational marketing theory and social capital theory, while practical implications suggest that MSME managers should prioritize network-building and knowledge-sharing to enhance international competitiveness.